Comparison of 10-day sequential therapy with 7-day standard triple therapy for Helicobacter pylori eradication in inactive peptic ulcer disease and the efficiency of sequential therapy in inactive peptic ulcer disease and non-ulcer dyspepsia. Issue 1 (December 2015) - Chan, Chung-Chuan; Chien, Nai-Hsuan; Lee, Chia-Long; Yang, Yi-Chen; Hung, Chih-Sheng; Tu, Tien-Chien; Wu, Chi-Hwa
Abstract Background Eradication rates of standard triple therapy forHelicobacter pylori infections have decreased in recent years due to a worldwide increase in bacterial resistance. Sequential therapy has the advantage of a two-phase treatment regimen and achieves a superior result forH. pylori eradication in peptic ulcer disease. However, no study has yet compared the efficacy of sequential therapy forH. pylori eradication exclusively in inactive duodenal ulcer (iDU) or non-ulcer dyspepsia (NUD). Method We retrospectively recruited 408 patients with endoscopic proven iDU (170 patients) or NUD (238 patients) infected withH. pylori . Patients with iDU were assigned into two groups: iDU triple therapy group, 44 patients treated with 40 mg pantoprazole, 1000 mg amoxicillin and 500 mg clarithromycin, twice daily for 7 days; iDU sequential therapy group, 126 patients treated with 40 mg pantoprazole and 1000 mg amoxicillin, twice daily for the first 5 days, followed by 40 mg pantoprazole, 500 mg clarithromycin and 500 mg tinidazole, twice daily for the next 5 days. All patients with NUD were treated with sequential therapy and assigned as the NUD sequential group. Post-treatmentH. pylori status was confirmed by a13 C-urea breath test. Result The eradication rates of intention-to-treat (ITT) and per-protocol (PP) analysis were 77.3 % (95 % CI 64.9–89.7 %) and 85.0 % (95 % CI 73.9–96.1 %) in the iDU triple therapy group and 87.3 % (95 % CI 81.5–93.1 %) and 92.4 % (95 % CI 87.6–97.2 %) in the iDU sequential therapy group. The overall eradication efficacy was superior in the sequential group than in the triple group, both with ITT analysis (83.5 %vs. 77.3 %, P = 0.29) and PP analysis (88.1 %vs. 85.0 %, P = 0.57). Eradication rates for ITT and PP analysis were 81.5 % (95 % CI 76.6–86.4 %) and 85.8 % (95 % CI 83.5–88.2 %) in the NUD sequential therapy group. Eradication rate was statistically better in the iDU sequential therapy group than the NUD sequential therapy group according to per protocol analysis (P = 0.04). Eradication rate was not significantly different between the iDU sequential- and iDU triple therapy groups according to protocol analysis (P = 0.14). Conclusion The sequential regimen has a better eradiation rate in the iDU group than in the NUD group. There is no statistically difference between 10-day sequential therapy and 7-day standard triple in iDU group.